2021
DOI: 10.3892/etm.2021.9884
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas alleviates acute alcohol‑induced liver injury by inhibiting JNK activation

Abstract: Binge alcohol drinking is fast becoming a global health concern, with the liver among the first organ involved and the one afflicted with the greatest degree of injury. Oxidative stress, alterations in hepatic metabolism, immunity and inflammation have all been reported to contribute to the development of alcoholic liver disease (ALD). Hydrogen gas (H 2) serves a key role in the modulation of hepatic redox, immune and inflammatory homeostasis. However, the effects of treatment using intraperitoneal injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…JNK is a key mediator in hepatic steatosis, where it regulates transcription factor activity associated with lipid metabolism. 25 Western blot analysis data demonstrated that the livers of ethanol-fed OLETF and LETO rats showed significantly decreased hepatic JNK phosphorylation (Figure 3E,F). Therefore, the protective effect of youth in rats (lasting till 16 weeks after birth) against alcohol-induced liver injury is hypothesized to be partially mediated by reducing JNK phosphorylation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…JNK is a key mediator in hepatic steatosis, where it regulates transcription factor activity associated with lipid metabolism. 25 Western blot analysis data demonstrated that the livers of ethanol-fed OLETF and LETO rats showed significantly decreased hepatic JNK phosphorylation (Figure 3E,F). Therefore, the protective effect of youth in rats (lasting till 16 weeks after birth) against alcohol-induced liver injury is hypothesized to be partially mediated by reducing JNK phosphorylation.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the upregulation of serum ALT and AST levels of OLETF rats after ethanol treatment indicated hepatocytic damage. JNK is a key mediator in hepatic steatosis, where it regulates transcription factor activity associated with lipid metabolism 25 . Western blot analysis data demonstrated that the livers of ethanol‐fed OLETF and LETO rats showed significantly decreased hepatic JNK phosphorylation (Figure 3E,F).…”
Section: Discussionmentioning
confidence: 96%